Analysis of inadequate cervical smears using Shewhart control charts - Wall Michael K; Mohammed Mohammed A; Harrison Wayne N; Marshall Tom P (BMC, 2004)
Abstract Background Inadequate cervical smears cannot be analysed, can cause distress to women, are a financial burden to the NHS and may lead to further unnecessary procedures being undertaken. Furthermore, the proportion of inadequate smears is known to vary widely amongst providers. This study investigates this variation using Shewhart's theory of variation and control charts, and suggests strategies for addressing this. Methods Cervical cytology data, from six laboratories, serving 100 general practices in a former UK Health Authority area were obtained for the years 2000 and 2001. Control charts of the proportion of inadequate smears were plotted for all general practices, for the six laboratories and for the practices stratified by laboratory. The relationship between proportion of inadequate smears and the proportion of negative, borderline, mild, moderate or severe dyskaryosis as well as the positive predictive value of a smear in each laboratory was also investigated. Results There was wide variation in the proportion of inadequate smears with 23% of practices showing evidence of special cause variation and four of the six laboratories showing evidence of special cause variation. There was no evidence of a clinically important association between high rates of inadequate smears and better detection of dyskaryosis (R2 = 0.082). Conclusions The proportion of inadequate smears is influenced by two distinct sources of variation - general practices and cytology laboratories, which are classified by the control chart methodology as either being consistent with common or special cause variation. This guidance from the control chart methodology appears to be useful in delivering the aim of continual improvement.